Rapid and qualitative identification of SARS-CoV-2 mutations associated with variants of concern using a multiplex RT-PCR assay coupled with melting analysis. (September 2022) - Sberna, Giuseppe; Fabeni, Lavinia; Berno, Giulia; Carletti, Fabrizio; Specchiarello, Eliana; Colavita, Francesca; Meschi, Silvia; Matusali, Giulia; Garbuglia, Anna Rosa; Bordi, Licia; Lalle, Eleonora
Highlights : In 94% of samples, Simplexa® Variant Direct was in agreement with the Sanger sequencing Simplexa® Variant Direct was useful in obtaining faster results (107 minutes) Simplexa® Variant Direct provides rapid and reliable alternative to sequencing Abstract: Objectives: Considering the spread of new genetic variants and their impact on public health, it is important to have assays that are able to rapidly detect SARS-CoV-2 variants. Methods: We retrospectively examined 118 positive nasopharyngeal swabs, first characterized by the Sanger sequencing, using the Simplexa® SARS-CoV-2 Variants Direct assay, with the aim of evaluating the performance of the assay to detect N501Y, G496S, Q498R, Y505H, E484K, E484Q, E484A, and L452R mutations. Results: A total of 111/118 nasopharyngeal swabs were in complete agreement with the Sanger sequencing, whereas the remaining seven samples were not amplified due to the low viral load. The evaluation of the ability of the assay to detect the E484Q mutation was performed using a viral isolate of the SARS-CoV-2 Kappa variant, showing concordance in 15/15 samples. Simplexa® SARS-CoV-2 Variant Direct assay was able to detect mutation pattern of Alpha, Beta, Gamma, Delta, and Omicron variants with 100% specificity and 94% sensitivity, whereas 100% sensitivity and specificity for the Kappa variant was observed. Conclusion: The assay can be useful to obtain faster results, contributing to a prompt surveillance of SARS-CoV-2 variants; however, it requires to be confirmed by the Sanger method, especially in the case of pattern of mutations that are different from those expected and also requires updates as new variants emerge.